Comparison of Bone Mineral Density in US Adults With Diabetes, Prediabetes and Normoglycemia From 2005 to 2018 - Yuan, Jing; Jia, Pu; Zhou, Jian-Bo (Frontiers in Endocrinology, 2022)
Background: Accumulated evidence have shown that diabetes have an impact on bone metabolism with conflicting results. Furthermore, little is known about the relationship of prediabetes with bone mineral density (BMD). Therefore, we explored the association between BMD and glucometabolic status in US adults. Methods: In this cross-sectional study, we extracted and analyzed data from National Health and Nutrition Examination Survey (NHANES) from 2005 to 2018. A total of 14610 subjects aged 40 ≥ years diagnosed with diabetes, prediabetes or normal glucose regulation (NGR), and have available data of BMD were eligible. Results: The prevalence of prediabetes and diabetes in US adults aged 40 ≥ years were 39.2% and 26.4%, respectively. After multivariable adjustment, we found an increasing trend of BMD at total hip, femoral neck and lumbar spine with glucometabolic conditions from NGR, prediabetes to diabetes in US adults ≥40 years. This trend was more prominent in women than in men. Fasting blood glucose and HbA1c were also demonstrated to be positively related to BMD. Conclusions: Glucometabolic conditions were significantly associated with BMD values in U.S. adults. Keywords: Diabetes; Prediabetes; Bone mineral density; Dual-energy X-ray absorptiometry; National Health and Nutrition Examination Survey